GOALS AND OBJECTIVES OF TEACHERS IN A CLASSROOM - Malohat Ergasheva (World Scientific Research Journal, 2025)
Annotation: This article explores the main goals and objectives of teachers in a classroom setting. It emphasizes the importance of setting clear, measurable, and achievable aims that guide both teaching and learning processes. The article also discusses how teachers’ goals influence student motivation, classroom management, and overall academic success.